(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2009)
The objective of this investigation was to evaluate the effects of a behavior-analysis therapist’s performance checklist on the performance of nine pairs of psychotherapists commencing advanced training. The therapists watched 13 videotapes of their own sessions and graded their performance on the checklist, following a multiple baseline design. Results indicated that this tool had a certain, positive effect on overall performance and particularly on performance related to the collection of data by the therapists and the establishment of a therapeutic alliance. In terms of performance related to intervention strategies, however, the results were not so positive. Observations were made in relation to other variables that could have influenced the results, such as clinical experience, supervisory style, type of clinical problem and validity/reliability of the tool.